Analisis Komprehensif Rasio Keuangan Pemerintah Daerah Dalam Menilai Stabilitas Fiskal Dan Struktur Pembiayaan: Studi Kasus Kota Pekalongan - aulia nailufar; Mahirun Mahirun (JURNAL LITBANG KOTA PEKALONGAN, 2026)
This study aims to analyze the financial performance of the Pekalongan City Government during the 2019–2024 period using regional financial ratio analysis. The ratios examined include financial independence, fiscal decentralization, local revenue (PAD) effectiveness, regional financial efficiency, expenditure harmony, revenue growth, and solvency ratios, including the debt to equity ratio (DER). The research method employed is descriptive quantitative, using a documentation study approach based on secondary data from the Budget Realization Report (LRA) and the regional government balance sheet. The findings indicate that the city demonstrates a high level of PAD effectiveness and maintains financial efficiency, although the allocation remains dominated by operational expenditures over capital expenditures. The financial independence and fiscal decentralization ratios are still relatively low, indicating dependence on central government transfers. Nevertheless, the financial structure shows significant improvement, as reflected in the declining solvency and DER ratios. This research provides a comprehensive overview of the fiscal stability and financial structure of the Pekalongan City Government and offers policy recommendations for more autonomous and sustainable regional financial management